Некоторые зоогеографические особенности антарктических островов Баллени - Корабельников, Л.В. (Вестник зоологии, 1975)
In the summer-autumn period ornitofauna of the Balleni Islands is of a mixed character: only certain species of birds can nest there. Birds, seals and whales are attracted by good food conditions of this region. Birds typical for temperate and subantarctic zones reach far southwards and at the same time the typical antarctic birds migrate slightly in the northern direction. 9 species (56.2%) of birds as well as seals are presented here by polar species, which gives grounds to consider the faunistic complex of the Balleni Islands as primarily antarctic one.